2021
DOI: 10.1186/s40729-021-00381-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of implant support for distal extension removable partial dentures: functional evaluation using occlusal force measurement and masticatory efficiency

Abstract: Background Implant-supported removable partial dentures (ISRPD) are supported at the free-end region with implant retainers. As implant retainers prevent denture settlement and facilitate denture retention, this is intended to improve masticatory performance in comparison with that of conventional removable dentures. In the present study, we evaluated the effect of implant retainers at the free-end region of removable dentures on occlusal force and masticatory efficiency using a pressure-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the current situation, Park et al concluded that masticatory movements in patients wearing IARPDs were significantly improved compared with patients wearing CRPDs for mandibular Kennedy classification I from a meta-analysis of these 3 clinical studies [8,33,41,49]. Murakami et al and Gonçalves et al also reported that bite force and mastication functions were significantly improved in patients receiving IARPDs compared to those receiving CRPDs [27,43]. Gonçalves et al showed that the masseter muscle during maximal clenching was significantly thicker in patients wearing IARPDs compared to those wearing CRPDs [43].…”
Section: Prosthetic or Technical Complicationsmentioning
confidence: 98%
See 4 more Smart Citations
“…In the current situation, Park et al concluded that masticatory movements in patients wearing IARPDs were significantly improved compared with patients wearing CRPDs for mandibular Kennedy classification I from a meta-analysis of these 3 clinical studies [8,33,41,49]. Murakami et al and Gonçalves et al also reported that bite force and mastication functions were significantly improved in patients receiving IARPDs compared to those receiving CRPDs [27,43]. Gonçalves et al showed that the masseter muscle during maximal clenching was significantly thicker in patients wearing IARPDs compared to those wearing CRPDs [43].…”
Section: Prosthetic or Technical Complicationsmentioning
confidence: 98%
“…In the present study, case series and reports were also included to acquire a broad range of clinical and basic information on IARPDs. Thirty-eight articles including systematic and literature reviews focused on clinical outcomes including survival rate, success rate, MBL, and complications of dental implants and IARPDs [8,[16][17][18][19][20][21][22]27,57,67,70,[72][73][74]127]. Thirty-four articles focused on types of dental implants (length, diameter, brands, and numbers) and biomechanics of IAR-PDs [36,67,71,75,[77][78][79][80]82,84,85,[87][88][89][90][91]93,[95][96][97][98][99][101][102][103][104][105][107][108][109][110]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 3 more Smart Citations